Effectiveness of green tea on decreasing the patient’s blood pressure and pulse rate patient before dental extraction - Ahyar Riza; Rahmi Syaflida; Indra B. Siregar; Ayu R. Nabila (Journal of Dentomaxillofacial Science, 2021)
Objective: To determine the effectiveness of green tea on reducing patient’s blood pressure and pulse rate before dental extraction in the Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Universitas Sumatera Utara. Material and Methods: This was an experimental quasi study with non-randomized pretest-posttest control group design. Purposive technique was used to select the subjects. The subjects were divided into 2 sample groups, each group consists of 18 patients. The control group were given warm water to drink before the dental extraction while the case group were given steeping green tea before the dental extraction. Blood pressure and pulse rate of each subjects were measured right after informed consent was given. The control group subjects were given to drink warm water while the case group subjects were given green tea steeping after the measurement of blood pressure and pulse rate. After 30 minutes, the blood pressure and pulse rate of each subjects were measured. Data obtained was statistically analyzed using Mann Whitney test and Wilcoxon test. Results: Blood pressure of pulse rate of the case group showed significant differences compared to the control group with a value of p = 0.000 <0.05. Conclusion: Steeping green tea was effective on reducing blood pressure and pulse rate in patients before tooth extraction.